Traumatyczna tęsknota za przeszłością (na materiale prozy Olgi Bergholc) - Pawletko, Beata (Studia Rossica Posnaniensia, 2019)
The article attempts to analyze the role of the Siege of Leningrad in life and works of Olga Bergholz. It is traumatic in the personal plan but at the same time extremely successful, intense and creative period. Thanks to radio broadcasts, Bergholz becomes the voice of the besieged Leningrad, raising the civilians of the city on the Neva, but work in the radio station is also a form of autotherapy. The importance of the siege in the poet’s life is also evident in the postwar period when it comes to claiming the memory of the victims.